Thermoluminescence kinetic parameters of proton-irradiated germanium doped flat-shape optical fibres - Hassan, M.F.; W.N., Rahman; Akagi, T.; Sulaiman, N.S.; Bradley, D.A. *; Noor, N. M. (Elsevier, 2023)
Glow curve is a key element in thermoluminescence (TL) studies as it provides on-the-ground understanding on the trapping mechanism inside the crystal lattice and hence stability of the TL material. In the present work, luminescence mechanism of the in-house fabricated germanium doped (Ge-doped) flat-shape silica optical fibres have been investigated following irradiation by 150-MeV proton beams. Results of TL dose-response showed that there is a linear relationship between TL response and proton doses from 1 to 10 Gy, with a coefficient of determination close to one. The structure of glow curve remains unchanged throughout the studied dose range with a maximum glow peak dominated at temperature of within 250–290 ◦C. A Tmax-Tstop plot reveals not only horizontal regions but also smooth slopes, indicative of the presence of a continuum distribution of glow peaks and trap depth. A computerised glow curve deconvolution analysis of the respective fibre glow-curves demonstrated that they were composed of five strongly overlapping peaks underlying a broad TL spectrum, obtaining figures of merit in the range of 0.56–1.64%. The main physical kinetic parameters (activation energy and frequency factor) of the fitted glow peaks were obtained using GlowFit software. The data suggest that the TL glow peaks of the Ge-doped silica optical fibres obey second-order kinetics.